Virtual Embodiment and Interaction Techniques in Virtual Reality Games - Cao, Jing (Transactions on Computer Science and Intelligent Systems Research, 2024)
Virtual Reality (VR) technology, characterized by immersive environments entirely generated by computers, has gained significant attention during the fifth information revolution. This paper explores the core elements of VR—Immersion, Interaction, and Imagination—as described by Burdea and Coiffet (1994). It emphasizes the importance of virtual embodiment in enhancing user experience within VR gaming. The development of technologies such as the CAVE system, head-mounted displays (HMDs), handheld controllers, haptic feedback devices, and full-body motion tracking systems are discussed in detail. Furthermore, the study delves into human-computer interaction (HCI) techniques crucial for immersive VR experiences and the principles of effective user experience (UX) evaluation. The significance of personalization and user comfort in VR environments, including addressing motion sickness and latency issues, is highlighted. This paper underscores the need for continuous improvement and user-centered design to optimize VR experiences. Ultimately, the paper suggests that VR technology’s future relies on balancing technical advancements with a deep understanding of user needs to create more immersive and satisfying virtual experiences.